2015
DOI: 10.1002/acr.22562
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Differences in Mortality and Cardiovascular Events Among Patients With End‐Stage Renal Disease Due to Lupus Nephritis

Abstract: Objective To identify racial and ethnic differences in mortality and cardiovascular (CV) risk among patients with end-stage renal disease (ESRD) due to lupus nephritis (LN) Methods Within the U.S. ESRD registry (1995-2008), we identified individuals aged >17 years with incident ESRD due to systemic lupus erythematosus (SLE). We ascertained demographics, clinical factors, and deaths from registry patient files and CV events (myocardial infarction, heart failure, hemorrhagic and ischemic strokes) from inpatien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 40 publications
(47 reference statements)
2
27
0
Order By: Relevance
“…Our Medicaid data were linked to USRDS, which captures nearly all ESRD cases in the US. While our findings may not be generalizable to all populations, we focused our study on a large, vulnerable, and diverse patient population, shown in other studies to have an excess burden of adverse outcomes, receiving care at both academic centers and non-academic centers (23,36,37). With 10 years of data and a mean follow-up of In this large, nationwide study of Medicaid beneficiaries with incident LN, we found extremely high rates of ESRD and mortality but no statistically significant differences by sex in these outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Our Medicaid data were linked to USRDS, which captures nearly all ESRD cases in the US. While our findings may not be generalizable to all populations, we focused our study on a large, vulnerable, and diverse patient population, shown in other studies to have an excess burden of adverse outcomes, receiving care at both academic centers and non-academic centers (23,36,37). With 10 years of data and a mean follow-up of In this large, nationwide study of Medicaid beneficiaries with incident LN, we found extremely high rates of ESRD and mortality but no statistically significant differences by sex in these outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Lupus nephritis (LN) is one of the hallmark features of SLE, seen in 40%–60% of patients at the moment of diagnosis, and is one of main causes of mortality among these patients [1]. Among 10 to 15% can develop an end stage renal disease during the follow-up and might require renal replacement therapies and/or kidney transplant [2, 3]. …”
Section: Introductionmentioning
confidence: 99%
“…African Americans with SLE were three times more likely to have CAD compared to Caucasians with SLE. Administrative studies have shown increased CAD in African Americans compared to Caucasians with SLE when restricting analyses to inpatient encounters and subsets of patients with SLE [35, 36]. Our study builds upon these studies by including all patients with SLE and capturing CAD in both inpatient and outpatient encounters.…”
Section: Discussionmentioning
confidence: 99%
“…There are fewer studies comparing risk of these cardiovascular diseases in African Americans to Caucasians with SLE, with mixed results [36, 37]. Specifically, in one cohort, there were no differences in rates of CVD and PVD comparing African Americans to Caucasians [39].…”
Section: Discussionmentioning
confidence: 99%